Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To solve the equation [tex]\(x^2 - 5x = 6\)[/tex] by factoring, follow these steps:
1. Rewrite the equation:
Start with the given equation:
[tex]\[ x^2 - 5x = 6 \][/tex]
2. Move all terms to one side:
Subtract 6 from both sides to set the equation to zero:
[tex]\[ x^2 - 5x - 6 = 0 \][/tex]
3. Factor the quadratic equation:
Look for two numbers that multiply to give the constant term ([tex]\(-6\)[/tex]) and add to give the coefficient of the linear term ([tex]\(-5\)[/tex]).
These two numbers are [tex]\(-6\)[/tex] and [tex]\(1\)[/tex], because:
[tex]\[ (-6) \cdot 1 = -6 \quad \text{and} \quad (-6) + 1 = -5 \][/tex]
Therefore, we can factor the quadratic as:
[tex]\[ (x - 6)(x + 1) = 0 \][/tex]
4. Set each factor equal to zero and solve for [tex]\(x\)[/tex]:
[tex]\[ x - 6 = 0 \quad \text{or} \quad x + 1 = 0 \][/tex]
Solve each equation:
[tex]\[ x = 6 \quad \text{or} \quad x = -1 \][/tex]
So the solutions to the equation [tex]\(x^2 - 5x = 6\)[/tex] are:
[tex]\[ x = \{ -1, 6 \} \][/tex]
These are the solutions that satisfy the original equation.
1. Rewrite the equation:
Start with the given equation:
[tex]\[ x^2 - 5x = 6 \][/tex]
2. Move all terms to one side:
Subtract 6 from both sides to set the equation to zero:
[tex]\[ x^2 - 5x - 6 = 0 \][/tex]
3. Factor the quadratic equation:
Look for two numbers that multiply to give the constant term ([tex]\(-6\)[/tex]) and add to give the coefficient of the linear term ([tex]\(-5\)[/tex]).
These two numbers are [tex]\(-6\)[/tex] and [tex]\(1\)[/tex], because:
[tex]\[ (-6) \cdot 1 = -6 \quad \text{and} \quad (-6) + 1 = -5 \][/tex]
Therefore, we can factor the quadratic as:
[tex]\[ (x - 6)(x + 1) = 0 \][/tex]
4. Set each factor equal to zero and solve for [tex]\(x\)[/tex]:
[tex]\[ x - 6 = 0 \quad \text{or} \quad x + 1 = 0 \][/tex]
Solve each equation:
[tex]\[ x = 6 \quad \text{or} \quad x = -1 \][/tex]
So the solutions to the equation [tex]\(x^2 - 5x = 6\)[/tex] are:
[tex]\[ x = \{ -1, 6 \} \][/tex]
These are the solutions that satisfy the original equation.
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.